Immunophenotyping to improve the mechanistic understanding of idiosyncratic drug-induced liver injury: clinical implications and future directions - Cueto Sánchez, Alejandro José; Di Zeo-Sánchez, Daniel Enrique; Segovia-Zafra, Antonio; Matilla-Cabello, Gonzalo; Bodoque-García, Ana; Lucena-González, María Isabel; Villanueva-Paz, Marina (Open Exploration, 2023)
The late event onset of a fraction of idiosyncratic drug-induced liver injury (DILI) cases and the link observed by genome-wide association studies (GWASs) of certain human leucocyte antigen (HLA) alleles with DILI due to specific drugs support the crucial role of the immune system (both innate and adaptive) in the pathogenesis of DILI. Recent advances in both flow and mass cytometry have allowed the profiling of all major immune cell types in a given sample. Therefore, determining the lymphocyte populations in samples from patients with DILI would facilitate the development of specific biomarkers for DILI diagnosis and prognosis. To date, a few studies have explored the immune landscape in DILI. In a recent study of leukocyte immunophenotyping using flow cytometry from the Spanish DILI Registry, an important role of adaptive immune response in DILI is suggested. DILI patients had significantly higher levels of T helper 1 (Th1) cells and activated helper and cytotoxic T cells than healthy controls. Furthermore, the increased expression of negative immune checkpoints and ligands in DILI patients could reflect a restoration of the immune homeostasis. Differences in the profile of cytokines in DILI patients from the Drug-Induced Liver Injury Network (DILIN) also suggest an involvement of both innate and adaptive immune systems in DILI development and prognosis. Moreover, several studies based on immunophenotyping of liver infiltrates showed a distinctive pattern of cellular infiltrates in patients with immune checkpoint inhibitors (ICIs)-DILI, with lower levels of plasma cells, CD20+ B cells and CD4+ T cells than in autoimmune hepatitis (AIH) patients. These pioneering studies highlight the importance of immunophenotyping for the mechanistic understanding of DILI. In this review, available data on immunophenotyping in DILI are gathered, and the potential clinical applications of cutting-edge, novel immunophenotyping techniques are discussed.
Keywords: Hepatotoxicidad; Hígado - Efectos de los medicamentos; Hígado - Enfermedades; Inmunodiagnóstico; Diagnóstico de laboratorio; Hepatotoxicity; Drug-induced liver injury (DILI); Immune tolerance; Immune system; Immunophenotyping; Diagnosis; Mechanisms